Cadena de valor del ecoturismo en el distrito de Sauce – San Martín - Lozano Reátegui, Shirley Natalie (2011)
In this context 1 raise the value ecotourism chain with the need to establish operational lines of action for the creation of Eco tourist products specialized and differentiated that will permit the development of Sauce ecotourism destination. Likewise, to guarantee the management of the activity Echo tourist in the area of the destination, the key actors have considered to be opportune and suitable to possess a Managing Entity ecotourism destination Sauce, validated and recognized with competences in the field of tourism, that assumes the task of coordinating with the San Martin Regional Government and Local Governments the actions to take in the destination in an integrated manner. Where it is meant to promote the Amazon identity, strengthening the capacity. of actors linked to tourism, to improve relations between the tourism sector and other sectors, to bring the value of the natural heritage, among others. Key words: ecotourism chain, ecotourism products.